Law, economics, and conflict - Basu, Kaushik, 1980-; Hockett, Robert (Cornell global perspectives., 2021)
"The rise in global conflict, dramatic technological breakthroughs, and the floundering of traditional law and economics has precipitated a reexamination of the fundamentals of law and economics. This volume focuses on the new challenges arising from globalization, technological advance, and the social and political conflicts to which they give rise. Its contributors mull over the challenges of this new world and how we can steer a course giving individuals the space and freedom to work, innovate, earn, profit and prosper, and the state the wisdom to regulate and ensure that conflicts do not occur, externalities are managed, and some are not marginalized and impoverished, while others accumulate and prosper"--Provided by publisher